Evaluation of In Vitro Cytotoxic Property Against Cholangiocarcinoma Cell Line and GC/MS Analysis from Leaf of Erythrophleum succirubrum Gagnep - Chaiyong S. (2023)
Objective: Plants are valuable sources of new pharmaceuticals. Secondary metabolites of the genus Erythrophleum exhibit cytotoxicity and may have therapeutic value. The cytotoxic activity of ethanolic leaf extract of Erythrophleum succirubrum Gagnep. against a human cholangiocarcinoma cell line was assessed. Methods: Crude extract of E. succirubrum was prepared by ethanol extraction. The ethanolic leaf extract of E. succirubrum was evaluated for cytotoxicity against the human cholangiocarcinoma cell line KKU-M213 using 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT) assays. The chemical composition of E. succirubrum leaf extract was analyzed using GC/ MS. Result: The ethanolic leaf extract of E. succirubrum reduced the viability of KKU-M213 cells in a dose and time-dependent manner. It showed high cytotoxicity, with IC50 values of 65.22 ± 1.18 μg/mL and 1.19 ± 1.38 μg/mL at exposure times of 24 and 96 h, respectively. GC/MS analysis of the ethanolic leaf extract of E. succirubrum identified 22 components. The main constituents identified were Cyclohexanone, 2-[2-nitro-1-(2-naphthyl)ethyl]-(14.79%) followed by allomycin (14.65%), mome inositol (14.30%), campesterol (11.80%) and ethyl linolenate (10.83%), respectively. Conclusion: Five major groups of compounds were found, with lipids dominating, followed by carbohydrates, benzenoids, phenylpropanoids, polyketides and organoheterocyclic compounds. Many of the bioactive components discovered in the ethanolic leaf extract of E. succirubrum might be responsible for its cytotoxic properties.